Biodiversity in the Global South Research for a sustainable world - Agnèse, Jean-François; Dangles, Olivier; Rodary, Estienne (Focus, 2020)
Designed to reach the widest possible audience, this volume showcases some of the research projects which best illustrate the commitment of the French National Research Institute for Sustainable Development (IRD) to biodiversity and sustainable development. Among today's many pressing environmental challenges, protecting biodiversity is probably one of the most complex, since it cannot be understood independently of its interactions with the human societies who live with it, use it, manage it, destroy and, occasionally, protect it. As the examples contained herein demonstrate, biodiversity can no longer be confined by narrow academic boundaries. On the contrary, it is a subject inextricably linked with all of the major dynamics, human and non-human, which shape the global and local changes we currently face. In this respect, the present volume is testament to the commitment demonstrated by IRD and its partners to a vision of scientific endeavour which yields tangible, utilisable knowledge for the Global South, sustainability science in the strongest sense of the term, allowing our planet and its biodiversity to thrive in the long term.